Body control in American cyberspace: a study on Don Delillo's White Noise - Babaee, Ruzbeh; Wan Yahya, Wan Roselezam; Bahar, Ida Baizura (Canadian Center of Science and Education, 2014)
Don DeLillo’s White Noise (1984) is a cyberpunk narrative commenting on dystopia of late capitalism by illustrating the instability of the apparently safe and perfect life of a small town in North America. The dystopian society in white Noise is not a hierarchal world or a world in another time and space, as it is common in most dystopian narratives. It is a world that we may experience in our daily life. This study attempts to demonstrate that DeLillo criticizes the condition of the late twentieth century in which human beings are entrapped and become disembodied in cyberspace. This study also reveals that human beings live in a state of suspension in cyberspace. Furthermore, it is of great significance for this study to show that cyberspace is a control system that manipulates human beings through their bodies in the contemporary world.